Transverse load carrying capacity of sinusoidally corrugated steel webs with web openings - Kıymaz, Güven; Coşkun, Erdal; SEÇKİN, EDİP (My University, 2010)
A study on the behavior and design of corrugated web steel beams with and without web openings is presented. In the literature, the web opening problem in steel beams was dealt with mostly for steel beams with plane web plates and research on the effect of an opening on a corrugated web was found out to be very limited. The present study deals mainly with the effect of web openings on the transverse load carrying capacity of steel beams with sinusoidally corrugated webs. A general purpose finite element program (ABAQUS) was used. Simply supported corrugated web beams of 2m length and with circular web openings at quarter span points were considered. These points are generally considered to be the optimum locations of web openings for steel beams. Various cases were analyzed including the size of the openings and the corrugation density which is a function of the magnitude and length of the sine wave. Models without web holes were also analyzed and compared with other cases which were all together examined in terms of load-deformation characteristics and ultimate web shear resistance.
Keywords: Sinusoidally corrugated web; web opening; web shear resistance; finite element analysis